'Kronic specifically attracts children': The construction of lay roles in New Zealand media reports on synthetic cannabis. (June 2016) - Barton, Josh
This paper explores the representations of non-expert 'lay' roles in selected media reporting of the 2011 synthetic cannabis debate in New Zealand. It uses a critical discourse analysis to explore these representations, using van Leeuwen's work on the transitivity of clauses. It identifies a number of roles present in reporting and argues that media reporting denies lay roles agency and limits the space available for their members to give their account of events. Instead lay groups are constructed as the passive recipients of actions by authoritative groups. The one exception to this is the construction of parents who, because of a combination of a moral authority granted to them by being parents, and the media's alignment to the 'concerned parent' position, are granted agency and space to explicate their positions.